Chemotherapy and advanced androgen blockage, alone or combined, for metastatic hormone-sensitive prostate cancer a systematic review and meta-analysis. (November 2022) - Fallara, Giuseppe; Robesti, Daniele; Nocera, Luigi; Raggi, Daniele; Marandino, Laura; Belladelli, Federico; Montorsi, Francesco; Malavaud, Bernard; Ploussard, Guillaume; Necchi, Andrea; Martini, Alberto
Highlights: The current standard of care of systemic treatment for metastatic hormone sensitive prostate cancer (mHSPC) includes androgen deprivation therapy (ADT) with either docetaxel or advanced androgen blockage (AAB) Two studies have tested the combination of ADT, docetaxel and AAB (triplet therapy) relative to docetaxel and ADT in this setting. We aimed to compare the effect on survival outcomes of available systemic treatments for mHSPC. Ten trials for a total of 5, 544 patients were included. We reconstructed survival data from published Kaplan-Meier curves on overall survival (OS) and progression free survival (PFS) and meta-analyzed docetaxel versus AAB versus triplet therapy (grouping together abiraterone/darolutamide and docetaxel). We found no OS nor PFS benefit for patients with mHSPC treated with triplet therapy compared to AAB alone, while an advantage emerged for both AAB or triplet therapy relative to docetaxel. Further studies are needed to better delineate the role of triplet therapy in the current treatment landscape. Abstract: Background: The current standard of care for the systemic treatment of metastatic hormone sensitive prostate cancer (mHSPC) includes androgen deprivation therapy (ADT) with either docetaxel or advanced androgen blockage (AAB). Recently, two studies have tested the combination of ADT, docetaxel and AAB (triplet therapy) relative to docetaxel and ADT in this setting. Herein, we aimed to compare the effect on survival outcomes of available systemic treatments for mHSPC. Methods: A comprehensive search for all published phase III randomized control trials on first line mHSPC that evaluated AAB (TITAN, ARCHES, STAMPEDE, LATITUDE, ENZAMET) or docetaxel (GETUG-AFU15, CHAARTED, STAMPEDE) or their combination (ARASENS, PEACE-1) was conducted PubMed, EMBASE, Web of Science, and Scopus databases up to 15/04/2022. We reconstructed survival data from published Kaplan-Meier curves on overall survival (OS) and progression free survival (PFS) and meta-analyzed docetaxel versus AAB versus triplet therapy (grouping together abiraterone/darolutamide and docetaxel). The outcomes of interest were assessed using differences in restricted mean survival time (ΔRMST) at different time points and Cox regression. Results: Ten trials were included involving 5, 544 patients for assessing OS and 5, 725 for PFS. Triplet therapy was associated with longer OS when compared to docetaxel (48-month ΔRMST: 2.6; 95 %CI: 1.8, 3.4; p < 0.001) but yielded similar OS when compared to AAB (48-month ΔRMST: −0.8; 95 % CI: −1.8, 0.2; p  = 0.1). Similarly, triplet therapy was associated with longer PFS when compared to docetaxel (48-month ΔRMST: 10.3; 95 %CI: 9.0, 11.6; p < 0.001) but yielded similar PFS when compared to AAB (48-month ΔRMST: 1.1; 95 %CI: −0.2, 2.3; p = 0.1). Conclusions: Overall, we found no OS nor PFS benefit for patients with mHSPC treated with triplet therapy compared to AAB alone, while an advantage emerged for both AAB or triplet therapy relative to docetaxel.